RESILIENSI PEREMPUAN TERHADAP PERMASALAHAN PENGGUNAAN NARKOBA DI KABUPATEN KEDIRI - Safa Intan Nurfadila; Taufiqurrohim Taufiqurrohim (Jurnal Harkat : Media Komunikasi Gender, 2023)
Abstract. Women and narcotics form a complex interplay within society. With the escalating issue of drug circulation and abuse, family resilience emerges as a crucial pillar in addressing this matter. However, women often grapple with discrimination and social stigma. This research aims to comprehend women's roles in preventing drug abuse in Kabupaten Kediri and the values they espouse. The research employs a qualitative descriptive approach involving field research, encompassing observations, interviews, and document analysis. The concept of power within Michel Foucault's Power Relations Theory is utilized to understand women's roles. The research reveals that women's roles in family resilience encompass four main aspects: Social Power Agents, Knowledge Transfer Agents, Social Support Agents, and Social Inclusivity Agents. This study provides valuable insights for addressing the drug problem in Kabupaten Kediri through the roles of women. Abstrak. Perempuan dan narkoba memiliki hubungan yang kompleks dalam masyarakat. Dalam menghadapi peningkatan masalah narkoba, ketahanan keluarga menjadi penting. Namun, perempuan sering menghadapi diskriminasi dan stigma sosial. Penelitian ini bertujuan untuk memahami peran perempuan dalam mencegah penyalahgunaan narkoba di Kabupaten Kediri dan nilai-nilai yang mereka terapkan. Metode penelitian adalah deskriptif kualitatif dengan observasi, wawancara, dan analisis dokumen. Konsep kuasa dalam Teori Relasi Kuasa Michael Foucault digunakan untuk memahami peran perempuan. Hasil penelitian menunjukkan peran perempuan dalam ketahanan keluarga sebagai Agen Kekuatan Sosial, Agen Penyampaian Pengetahuan, Agen Dukungan Sosial, dan Agen Inklusivitas Sosial. Penelitian ini memberikan wawasan untuk mengatasi masalah narkoba di Kabupaten Kediri melalui peran perempuan.